Ghana's Foreign Policy, 1957-1966 : Diplomacy Ideology, and the New State - Thompson, Willard Scott (Princeton, NJ : Princeton University Press, 2015)
A systematic and thorough analysis of a small, determined and comparatively wealthy "new" state's attempts to enlarge its influence and augment its power.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- ACKNOWLEDGMENTS -- PREFACE -- SOME OF THE ACTORS -- Organizational Listing and Abbreviations -- CONTENTS -- I. Opportunities, 1957-1960 -- 1. INTRODUCTORY PREVIEW -- 2. DIPLOMATIC STIRRINGS, March 1957-October 1958 -- 3. AFRICAN LIBERATION, November 1958-June 1960 -- II. "Diplomatic Cockpit", JULY 1960-JULY 1962 -- 4. THE CONGO CRISIS AND ITS REPERCUSSIONS, July 1960-February 1961 -- 5. EAST, WEST, AND NONALIGNMENT, July 1960-July 1962 -- 6. POLICY IN AFRICA: Diplomats Versus Militants, April 1961-July 1962 -- III. Union Government and Scientific Socialism, AUGUST 1962-FEBRUARY 1966 -- INTRODUCTION -- 7. EXTERNAL RELATIONS: The Limiting of Ghana's Options, August 1962-September 1964 -- 8. THE OAU AND THE "AFRICAN REVOLUTION" August 1962-July 1964 -- 9. DIPLOMATIC CONSEQUENCES, August 1964-February 1966 -- 10. "THE PENALTY OF FAILURE" -- APPENDICES AND INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: POLITICAL SCIENCE / International Relations / General